Religious communities of the Near East from Roman to Islamic rule: sectarianism and identity in an age of transition (5th-8th C) - Ehinger, J (2015)
This study endeavors to set Christian writing about Islam from the period of the Islamic expansion in the broader context of Christian theological development in Late Antiquity. To this end, this study traces elements of continuity in Christian thought from the Christological debates of the fifth and sixth century, particularly from the Council of Chalcedon in 451and the resulting emergence of the communities of Chalcedonians and anti-Chalcedonian Monophysites as the dominant strands of Christianity in the Near East at the rise of Islam. In order to understand how Christians began to integrate the Islamic expansion into their thinking, this study focuses particularly on Christian writings about Islam and the descriptions of Muslims in Christian writings from the rise of lslam, through the seventh and early eighth centuries, up to the Abbasid revolution in 750. It also considers the contemporary descriptions of Christians in the Qur'an, in order to illustrate that these descriptions have both a different starting point and a different focus, suggesting that both Christian discussions about Muslims and Muslim discussions about Christians were internal discussions, taking place within each tradition, and do not represent true inter religious dialogue. In this way, this study attempts to illustrate how the rise of lslam, the emergence of the caliphate and the resulting separation of the Near Eastern churches from the Christian hierarchy in Rome and Constantinople influenced Christian identity in the Near East. The writings of the seventh century, and the Christian identity they preserve, emerge as a hybrid, integrating elements of the competing, pre-Islamic concerns of doctrinal purity versus church unity, but also attempting to address, in a variety of ways, the initial fear over Muslim victory and the eventual acceptance of Muslim rule as the new status quo in the Near East